Characteristics and Prevention of the Debris Flows following Wenchuan Earthquake in Jushui River Basin, An County, China. (17th December 2014) - Ge, Yonggang; Zhang, Jianqiang; Guo, Xiaojun
Abstract : After analysing the catastrophic debris flows on August 18, 2012, and on July 9, 2013, in Jushui River basin, An County, the Wenchuan Earthquake seriously striken areas, it was found that they were characterized by the clay soil content of 0.1~1.2%, the density of 1.68~2.03 t/m 3, the discharges of 62.2 m 3 /s to 552.5 m 3 /s, and the sediment delivery modulus of 1.0~9.4 × 10 4  m 3 /km 2 . Due to intense rainstorm, many large debris flows produced hazard chain, involved in flash flood, debris flow, dammed lake, and outburst flood, and rose Jushui River channel about 1~4 m as well as amplified flood. The hazards and losses mainly originated from the burying and scouring of debris flows, flood inundating, and river channel rise. The prevention of debris flows is facing the intractable problems including potential hazard identification, overstandard debris flow control, control constructions destructing, and river channel rapid rise. Therefore, the prevention measures for the basin, including hazard identification and risk assessment, inhabitants relocating, monitoring and alarming network establishing, emergency plans founding, and river channel renovating, and the integrated control mode for watershed based on regulating the process of debris flow discharge, were recommended for mitigation.